Analisis Sedimentasi Pada Saluran Drainase Sepanjang 3,1 Km Di Kawasan Lau Dendang Medan - Surbakti, Maria Yosep Hane; Sinaga, Rachel Eshia; Yolanda, Yuni (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
This study aims to evaluate sedimentation conditions and the performance of a drainage channel along approximately 3.1 km in the Lau Dendang area, Medan. To achieve this objective, the research was conducted through field surveys involving direct measurements at 10 observation points to obtain data on channel geometry and sediment thickness. In addition, supporting analyses were carried out through population projections using arithmetic, geometric, and exponential methods, as well as rainfall analysis using Gumbel, Log Normal, and Log Pearson Type III distributions. The results show that the total sediment volume reaches approximately 910.38 m³, which significantly reduces the channel’s storage capacity. The uneven distribution of sediment indicates the influence of local activities as well as variations in flow characteristics across different segments. Rainfall analysis shows that the Gumbel method produces the highest values compared to other methods, making it more representative for extreme rainfall conditions. On the other hand, population growth leads to an increase in domestic wastewater discharge of up to approximately 14.41 million liters per day, which further accelerates the sedimentation process within the channel. Based on these findings, it can be concluded that drainage problems in the study area are influenced not only by hydrological factors but also by domestic activities. Therefore, an integrated drainage management approach is required, including routine maintenance and proper domestic waste control, to ensure optimal channel performance.